Tingkat Kecemasan Orang Tua tentang Pembelajaran Daring pada Anak Berkebutuhan Khusus di Masa Pandemi Covid-19 - Tiyas Budi Hanggraeni; Atika Dhiah Anggraeni (Faletehan Health Journal, 2022)
Covid-19 pandemic in Indonesia had affected various fields, especially education. The Ministry of Education and Culture took a policy for the implementation of learning carried out from home or online. This condition led some parents of children with special needs to anxiety. The aim of this study was to determine the correlation between parents' anxiety levels on online learning and the knowledge of children with special needs during the COVID-19 pandemic. This was a quantitaive study with a cross-sectional approach. The samples of this study were parents of children with special needs with a total of 65 respondents who were selected by using a cluster random sampling technique. The results showed that the anxiety level of parents on online learning was in mild category (50.8%). Meanwhile, the knowledge of children with special needs during covid-19 pandemic was mostly in low category (90.8%). The results of the analysis showed that there was a relationship between parent's anxiety level and the knowledge of children with special needs during Covid-19 pandemic.